ISSUES OF ENLIGHTENMENT IN THE ACTIVITIES OF THE JADIDS - Ashurov N. B. (Web of Journals Publishing, 2024)
The article provides information about the activities of the Jadids and their views on the education of a harmoniously developed generation.
Keywords: Jadids, Jadids, Soviet system, ideology, enlightenment, economic pressures.